Maudu Lompoa in the Trajectory of History: Continuity of Tradition and Socio-Economic Impact in Cikoang (2019–2024) - Nurul Hidayanti Syarif; Ashari Ismail; M. Rasyid Ridha; Bakhtiar Bakhtiar (Journal of General Education and Humanities, 2026)
The preservation of the Maudu Lompoa tradition in Cikoang Village, Takalar Regency, South Sulawesi, faces significant challenges due to economic mobility, population migration, and pressures from globalization during the 2019–2024 period. These socio-economic dynamics threaten the continuity of intangible cultural heritage, particularly in the transmission of intergenerational values and in community participation patterns. This study aims to examine (1) the forms of community adaptation in maintaining the Maudu Lompoa tradition, (2) the role of the tradition in strengthening cultural identity and social resilience, and (3) its socio-economic impacts on the Cikoang community during 2019–2024. This study employed a qualitative approach combining ethnographic and historical methods, applying the stages of heuristics, source criticism, interpretation, and historiography. Data were collected through in-depth interviews with traditional leaders, Sayyid groups, and non-Sayyid community members; participant observation of the ritual procession; and secondary documentary sources. Purposive and snowball sampling were used until data saturation was achieved, and the data were analyzed using inductive thematic analysis and triangulation. The results reveal that the Cikoang community adapts through cross-generational value transmission and flexible symbolic participation—such as migrants contributing via remittances or family representatives. The tradition functions as a mechanism for collective identity formation through Islamic-local cultural syncretism and strengthens social resilience through mutual cooperation (gotong royong). Socio-economically, the tradition generates local economic turnover through ritual-related consumption and reinforces a values-based economic ethic grounded in spiritual blessings, sincerity, and communal solidarity. These findings indicate that tradition sustainability is achieved through dynamic cultural negotiation rather than rigid preservation, with implications for cultural tourism policy development in Takalar Regency.